Laboratory measure of cheating predicts misbehavior at school - Alain Cohn; Michel André Maréchal (University of Zurich, Department of Economics, 2015)
We study the external validity of a standard laboratory measure of cheating. The results show that cheating in the lab significantly predicts classroom misbehavior in middle and high school students.
Keywords: C93; K42; 330; Cheating; Honesty; Experiment; External Validity; Misbehavior